Oxidation and metasomatism of lithospheric mantle beneath the southern South America - Wang, Jian (University of Ottawa (Canada), 2007)
Quaternary basalts in the Cerro del Fraile area contain two types of mantle xenoliths; coarse-grained (2-5 mm) C-type spinel harzburgites and lherzolites, and fine-grained (0.5-2 mm) intensely metasomatized F-type spinel lherzolites. C-type xenoliths show high Mg in olivine (Fo = 90-91) and a range in Cr# (0.17-0.34) in spinel. Two C-type samples contain solidified patches of melt that is now composed of minute grains of plagioclase + Cr-spinel + clinopyroxene + olivine. These patches of melts formed from pargasitic amphibole by decompression melting. High Ti contents and occurrence of relict Cr-spinel in these melts indicate that the amphibole formed from spinel by interaction with the Ti-rich parental magma of the websterite veinlets. The fO2 values of these two C-type xenoliths are low, ranging from DeltaFMQ-0.2 to -0.4, consistent with their metasomatism by an asthenospheric mantle-derived melt. The rest of the C-type samples are free of patch "melt", but show cryptic metasomatism by slab-derived aqueous fluids, which produced high concentrations of fluid-mobile elements in clinopyroxenes, and higher fO2 ranging from DeltaFMQ +0.1 to +0.3. Low Mg# values of silicate minerals including the amphibole, together with the high ratios of Sr/Y and light rare earth elements (REE)/heavy REE in clinopyroxenes, suggest that the metasomatic agent was most likely a slab melt. F-type xenoliths show relatively low fO2 (AFMQ-0.9 to -1.1) compared to C-type xenoliths and this is explained by the fusion of organic-rich sediments overlying the slab during the slab melt. The fusion of such wet sediments likely produced CH4-rich fluids and reduced melts, that mixed with the slab melt. High U and Th in bulk rocks and clinopyroxene support the proposed interpretation. Mantle xenoliths in the Quaternary Pali Aike alkaline basalts include lherzolites and harzburgites with and without garnet. The texture and mineralogy suggest that garnet peridotites formed from spine! peridotites due to cooling and/or pressure increase during or after stablization below the Paleozoic continental crust. The values of fO2 for the entire Pali Aike xenolith samples range from FMQ-0.33 to +0.75, which overall overlap those of abyssal peridotites, are lower than those for sub-arc mantle peridotites. The fO2 data, together with the bulk rock major- and trace-element data, suggest that the subcontinental mantle lithosphere below Pali Aike formed through the accretion of oceanic lithosphere. The metasomatism observed in the Pali Aike xenoliths reflect recent infiltration of asthenosphere-derived melt through a slab window. The metasomatism resulted in the formation of Ti-phlogopite, Ti-amphibole, and ilmenite, and lowering of Mg and enrichment of Ti in bulk rocks and minerals. Extensive metasomatism also led to the replacement of olivine by orthopyroxene, forming orthopyroxenites. There are no discernible variations in fO2 values between spinel- and garnet- facies peridotites and between metasomatized and non-metasomatized samples, suggesting the transformation process from spinel to garnet, and the infiltration of metasomatizing melt were not accompanied by changes of fO2. Pyroxenites are mainly garnet orthopyroxenites with minor olivine websterites. Orthopyroxenites contain minor, but common Ti-rich minerals and relict grains of olivine and clinopyroxene in secondary orthopyroxene and along the grain boundaries of orthopyroxene. The textural evidence suggests that secondary orthopyroxene in Pali Aike formed at the expense of olivine and clinopyroxene in garnet bearing harzburgites and lherzolites. The secondary orthopyroxene contains abundant fluid inclusions, relatively high TiO2 (0.20 - 0.59 wt%), moderate Al2O3 (2.87 - 5.10 wt%) and Cr 2O3 (0.09 - 0.48 wt%), and low Mg# (0.845 - 0.892) compared with orthopyroxene in garnet bearing peridotites in the area. The orthopyroxenite was likely formed from garnet bearing peridotites during extensive metasomatism by a Ti-rich melt. Injection of the melt also produced garnet orthopyroxenite veinlets with diffuse boundaries in peridotites. The mineralogy and mineral chemistry of veinlets are similar to those of discrete xenoliths, suggesting that orthopyroxenites form veins and veinlets in peridotites and that discrete orthopyroxenite xenoliths likely represent wide veins in peridotites. The concentrations of Cr, Ni and PGE in orthopyroxenites are high and similar to those of peridotites, suggesting that they are essentially immobile during the metasomatism and that the evolved metasomatizing melt did not introduce these elements to the orthopyroxenites. The melt brought alkalis, Ti, Si, Al, Cu, and S to the orthopyroxenites. (Abstract shortened by UMI.)
Keywords: Geology.